ANALISIS PENENTUAN KRITERIA MISKIN SEBAGAI MUSTAHIK ZAKAT PADA BAITUL MAL MASJID NURUL HUDA DESA KELUMPANG JAYA KABUPATEN MUSI RAWAS UTARA - Behy Rosalia; Usdeldi Usdeldi; Sri Rahma (Institut Agama Islam Negeri Kerinci, 2023)
This study aims to determine the method used by the Baitul Mal Nurul Huda Mosque in Kelumpang Jaya Village North Musi Rawas Regency in determining the criteria for poor mustahik and the inhibiting factors in determining the criteria for poor mustahik. This research is of a qualitative type. The object of this research is all the administrators of the Baitul Mal Masjid Nurul Huda, Kelumpang Jaya Village North Musi Rawas Regency. The data sources used are primary data and secondary data. Data were obtained directly from 11 respondents using data analysis methods, namely observation, interviews, and personal documentation, then the data was processed using data processing techniques. The results showed that: In determining mustahik zakat, the Baitul Mal Masjid Nurul Huda Kelumpang Jaya Village North Musi Rawas Regency carried out a very selective process. The Baitul Mal Masjid Nurul Huda in determining mustahik candidates by collecting data obtained from the village head, then continuing with a direct survey of the field and making final recommendations, then holding deliberations with community representatives.